STRATEGI PENGEMBANGAN USAHA BERBASIS TEKNOLOGI BAGI WIRAUSAHA MUDA - Qarinaturrahmah Siregar; Muthia Latifah; Jeremia Renhard Tampubolon; Nurul Khalila Pohan; Intan Sari; Raihana Syahira (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2026)
The development of digital technology in the era of industrial transformation has driven significant changes in business patterns and strategies, including for young entrepreneurs. Technology is not only a support but also a crucial foundation for marketing, operations, and business development. This study aims to analyze the use of technology by young entrepreneurs, identify the obstacles they face, and formulate effective technology-based business development strategies. The study used a qualitative approach with descriptive methods, involving five young entrepreneurs aged 19–32 who had been running technology-based businesses for at least one year. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña model The research results show that technology is being utilized in various aspects, such as digital marketing through Instagram, TikTok, and marketplaces; operational management using cashier applications, Trello, and Google Business; and strengthening branding through digital content. However, young entrepreneurs still face obstacles such as low digital literacy, limited content editing skills, changes in social media algorithms, and limited capital for digital advertising. Business development strategies identified include consistent content creation, improving digital competency through independent training, and selecting digital platforms appropriate to their business type. This study concludes that technology plays a central role in the development of young entrepreneurs, but its effectiveness depends heavily on digital literacy, creativity, and adaptive strategies. Optimizing digital competencies and utilizing appropriate platforms are key to young entrepreneurs' success in facing competition in the digital economy.